Improving the Predictive Value of Preclinical Studies in Support of Radiotherapy Clinical Trials - Coleman, C Norman; Higgins, Geoff S; Brown, J Martin; Baumann, Michael; Kirsch, David G; Willers, Henning; Prasanna, Pataje G S; Dewhirst, Mark W; Bernhard, Eric J; Ahmed, Mansoor M (Clinical cancer research, 2016)
There is an urgent need to improve reproducibility and translatability of preclinical data to fully exploit opportunities for molecular therapeutics involving radiation and radiochemotherapy. For in vitro research, the clonogenic assay remains the current state-of-the-art of preclinical assays, whereas newer moderate and high-throughput assays offer the potential for rapid initial screening. Studies of radiation response modification by molecularly targeted agents can be improved using more physiologic 3D culture models. Elucidating effects on the cancer stem cells (CSC, and CSC-like) and developing biomarkers for defining targets and measuring responses are also important. In vivo studies are necessary to confirm in vitro findings, further define mechanism of action, and address immunomodulation and treatment-induced modification of the microenvironment. Newer in vivo models include genetically engineered and patient-derived xenograft mouse models and spontaneously occurring cancers in domesticated animals. Selection of appropriate endpoints is important for in vivo studies; for example, regrowth delay measures bulk tumor killing, whereas local tumor control assesses effects on CSCs. The reliability of individual assays requires standardization of procedures and cross-laboratory validation. Radiation modifiers must be tested as part of clinical standard of care, which includes radiochemotherapy for most tumors. Radiation models are compatible with but also differ from those used for drug screening. Furthermore, the mechanism of a drug as a chemotherapeutic agent may be different from its interaction with radiation and/or radiochemotherapy. This provides an opportunity to expand the use of molecular-targeted agents. Clin Cancer Res; 22(13); 3138-47. ©2016 AACR.